THE EFFECT OF PERCEIVED VALUE AND MOBILE GAME LOYALTY ON IN-APP PURCHASE INTENTION IN MOBILE GAME IN INDONESIA (CASE STUDY: MOBILE LEGEND AND LOVE NIKKI) - Purnami, Luh Dyah; Agus, Anna Amalyah (UI Scholars Hub, 2021)
Manuscript type: Empirical Research Research Aims: Investigate the effect of perceived value and mobile game loyalty on in-app purchase intention using case study male dominated game and female dominated game Design/methodology/approach: Conslusive descriptive research using Structural Equation Modelling Two-way approach Research Findings: It is found that on male dominated game and female dominated game economic value, social value, and game loyalty significantly influence in-app purchase intention. While on male dominated game loyalty is influenced by emotional values, social values and economic values. On the other hand, loyalty in female dominated game is influenced by emotional value, quality value, social value, and economic Theoretical Contribution/Originality: Provide insight regarding value that drive in-app purchase intention on freemium game in gender domination context Practitioner/Policy Implication: Provide insight to improve freemium game and contribute to give understanding on consumer behaviour primary in gaming context Research limitation/Implications: limited to particular game type (mobile game) and does not involved perceived risk in research framework